Семантико-стилістичний потенціал термінів у творах Й. Г. Струцюка про долю холмщаків - Масюк, Жанна; Masuk, Zhanna (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті розглянуто функціонування теонімів у творах Й. Г. Струцюка про долю холмщаків, виявлено їхні структурні, функціональні та семантичні особливості. Дослідження показало, що в художній спадщині волинського письменника вжито усталені найменування Бога, які в контексті набувають оригінальних конотацій. This article is dedicated to analysis the theonyms in the work of Volyn writer Strutsyuk J.G. This type of own names is distinguished by particularly expressiveness, as behind their referents appears complexes of philosophical and religious beliefs. In the investigation was examined the structural and semantical particularities of onyma God, and was found nominative, differential, localizing, emotional and allusive functions. The theonyms used in the work of J.G. Strutsyuk disclose the Christian worldview's fundamentals of the author and special by proper understanding of the religious experience of God. The results of the investigation showed that the style of this language units in the texts based on their traditional using in folk speech and confessional style.
Semantic and Stylistic Potential of the Theonyms in the Strutsyuk`s J.G. Works about Kholmshchyna
Keywords: Бог; денотат; сакральна онімія; теонім; Холмщина; God; denotation; sacral onyms; theonym; Kholmshchyna